Climate Change Scenarios of Precipitation Extremes in the Carpathian Region Based on an Ensemble of Regional Climate Models - Ladislav Gaál; Romana Beranová; Kamila Hlavčová; Jan Kyselý (Advances in Meteorology)
The study examines projected changes in precipitation extremes, aggregated on several time scales (1 hour, 1 day, and 5 days), in simulations of 12 regional climate models (RCMs) with high spatial resolution (~25 km). The study area is the Carpathian Basin (Central and Southeastern Europe) which has a complex topography and encompasses the whole territory of Slovakia and Hungary as well as major parts of Romania and western Ukraine. We focus on changes in mean seasonal maxima and high quantiles (50-year return values) projected for the late 21st century (time slice 2070–2099) in comparison to the control period (time slice 1961–1990), for summer and winter. The 50-year return values are estimated by means of a regional frequency analysis based on the region-of-influence method, which reduces random variability and leads to more reliable estimates of high quantiles. In winter, all examined characteristics of precipitation (seasonal totals, mean seasonal maxima, and 50-year return values for both short-term and multi-day aggregations) show similar patterns of projected increases for the late 21st century. In summer, by contrast, drying is projected for seasonal totals in all RCMs while increases clearly prevail for the 50-year return values. The projected increases are larger for short-term (hourly) extremes that are more directly related to convective activity than multiday extremes. This suggests that the probability of occurrence of flash floods may increase more than that of large-scale floods in a warmer climate. The within-ensemble variability (and associated uncertainty) is, nevertheless, much larger in summer than in winter.